Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have to determine the following:

$\lim\limits_{x \uparrow 1} \exp (-\sum\limits_{n=0}^{\infty}x^n)$

My idea is the following:

$\lim\limits_{x \uparrow 1} \exp (-\sum\limits_{n=0}^{\infty}x^n) = \lim\limits_{x \uparrow 1} \exp (-\frac{1}{1-x^n})$=...

share|cite|improve this question
You should have $\frac{1}{1-x}$ instead of $\frac{1}{1-x^n}$. Then, what is the conclusion of your idea? – Antonio Vargas Dec 8 '13 at 23:32

By continuity of $\exp$ $$\lim_{x \uparrow 1} \exp \left(- \sum_{n=0}^\infty x^n \right)=\exp \left( \lim_{x \uparrow 1} - \sum_{n=0}^\infty x^n \right)=\exp \left( \lim_{x \uparrow 1} \frac{1}{x-1} \right)=\exp(-\infty)=0. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.